Index modulation for 5G wireless communications - Wen, Miaowen; Cheng, Xiang (Researcher in wireless communication); Yang, Liuqing (Professor of computer engineering) (Springer, 2017)
"This book presents a thorough examination of index modulation, an emerging 5G modulation technique. It includes representative transmitter and receiver design, optimization, and performance analysis of index modulation in various domains. First, the basic spatial modulation system for the spatial domain is introduced. Then, the development of a generalized pre-coding aided quadrature spatial modulation system as well as a virtual spatial modulation system are presented. For the space-time domain, a range of differential spatial modulation systems are examined, along with the pre-coding design. Both basic and enhanced index modulated OFDM systems for the frequency domain are discussed, focusing on the verification of their strong capabilities in inter-carrier interference mitigation. Finally, key open problems are highlighted and future research directions are considered. Designed for researchers and professionals, this book is essential for anyone working in communications networking, 5G, and system design. Advanced-level students of engineering and computer science interested in efficiency techniques will also find the content valuable"--Provided by publisher.
Keywords: Cell phone systems -- Standards.; Wireless communication systems -- Standards.; Computer networks.; Electrical engineering.; elektronické knihy; electronic books